Pulsed Laser Targeting and Stirring for the Synthesis of (Au- Cu) NanoAlloy from Monometallic Colloids - Yousra A. Hussein; Jassim M. Mansour (Genius Journals, 2022)
The goal of this work has been to investigate the development of alloyed gold–copper nanoparticles (50%Au-50%Cu NPsunder simultaneous laser exposure and ultrasonic of colloids.(Au-Cu) compsit nanoparticle colloids by Laser ablation has been used as a feed for the dual method. The properties of produced particles are highly affected by experimental conditions such as churning and laser settings, including th e NPs size, form, content, and stability. A homogenous alloy and a core-shell structure of alloy nanoparticles containing (Au 50%: Cu 50%). To accomplish this, bulk targets were ablated with 1064 nm wavelength Nd: YAG laser in awater(DW) environment. Ultraviolet-visible optical absorption spectrometry, (TEM), (XRD) and FE-SEM and EDS
Keywords: Laser ablation; Alloyed Au-Cu nanoparticles; exposure; Mechanical mixing